519.7:531.3:677 DETERMINING OPTIMAL PARAMETER RATIOS IN THE STUDY OF LONGITUDINAL VIBRATIONS OF THREADS IN WEAVING PROCESS USING A MODEL - Adizova, Aziza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
During the formation of the fabric, various dynamic processes took place, including fluctuations in the threads. The article covers the technology of computer modeling of technological processes on example of the research of transverse oscillations of the thread in weaving process. As an example, the longitudinal oscillations and tension of the threads in the process of surf on a loom are considered.